2012
DOI: 10.1371/journal.pone.0040789
|View full text |Cite|
|
Sign up to set email alerts
|

Innate Immune Activation by Inhaled Lipopolysaccharide, Independent of Oxidative Stress, Exacerbates Silica-Induced Pulmonary Fibrosis in Mice

Abstract: Acute exacerbations of pulmonary fibrosis are characterized by rapid decrements in lung function. Environmental factors that may contribute to acute exacerbations remain poorly understood. We have previously demonstrated that exposure to inhaled lipopolysaccharide (LPS) induces expression of genes associated with fibrosis. To address whether exposure to LPS could exacerbate fibrosis, we exposed male C57BL/6 mice to crystalline silica, or vehicle, followed 28 days later by LPS or saline inhalation. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In support of the present hypothesis, 5-day inhalation exposure (2.5 h/day) to E. coli LPS aerosol (0.5 lg/m 3 ) exacerbated silicosis in mice (Brass et al, 2012), although it has been demonstrated that 5-day inhalation exposure (4 h/ day) to the same LPS aerosol alone (0.21 lg/m 3 ) induced BALF IL-1b in normal mice (Brass et al, 2003). In addition, a significant amount of LPS (120 ± 64 ng of E. coli LPS equivalent) was found in cigarette smoke (Hasday et al, 1999), which is well acknowledged as a risk factor for silicosis (WHO, 2000) and other idiopathic pulmonary fibrosis (Kim et al, 2006;Meltzer & Noble, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…In support of the present hypothesis, 5-day inhalation exposure (2.5 h/day) to E. coli LPS aerosol (0.5 lg/m 3 ) exacerbated silicosis in mice (Brass et al, 2012), although it has been demonstrated that 5-day inhalation exposure (4 h/ day) to the same LPS aerosol alone (0.21 lg/m 3 ) induced BALF IL-1b in normal mice (Brass et al, 2003). In addition, a significant amount of LPS (120 ± 64 ng of E. coli LPS equivalent) was found in cigarette smoke (Hasday et al, 1999), which is well acknowledged as a risk factor for silicosis (WHO, 2000) and other idiopathic pulmonary fibrosis (Kim et al, 2006;Meltzer & Noble, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…Bleomycin is metabolized in the lung, leading to a decrease in neutrophilic inflammation and a fibrotic response that spontaneously resolves after 2 to 3 months (Walters and Kleeberger, 2008). In the silica model, the stimulating crystals are not cleared from the lung, leading to ongoing inflammation, granuloma formation, and progressive fibrosis (Callis et al, 1985;Brass et al, 2012). In our study, Total lung collagen was determined by Sircol assay in lung homogenate (H).…”
Section: Discussionmentioning
confidence: 72%
“…Silica-induced lung inflammation and granuloma formation are reduced by the administration of TNF inhibitors or in animals deficient in TNF-α receptors [14][16]. The exacerbation of innate immune responses by repeated LPS exposure also amplifies the granulomatous response to silica in mice [17]. Finally, systemic inhibition of NF-kappa B activation with a pharmacological inhibitor decreases the severity of experimental silicosis [18].…”
Section: Introductionmentioning
confidence: 99%